2016
DOI: 10.3831/kpi.2016.19.033
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Zebrafish Model - A Well-Established Method for Rapidly Assessing the Toxicity of Homeopathic Drugs - Toxicity Evaluation of Homeopathic Drugs Using Zebrafish Embryo Model -

Abstract: Objectives:Advancements in nanotechnology have led to nanoparticle (NP) use in various fields of medicine. Although the potential of NPs is promising, the lack of documented evidence on the toxicological effects of NPs is concerning. A few studies have documented that homeopathy uses NPs. Unfortunately, very few sound scientific studies have explored the toxic effects of homeopathic drugs. Citing this lack of high-quality scientific evidence, regulatory agencies have been reluctant to endorse homeopathic treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Among the different in vivo models, zebrafish catches huge attention for preclinical [ 27 ] and toxicological studies [ 28 ] due to its higher homology with the human genome [ 29 ]. Numerous reports suggest that assessing the preclinical efficacy of small molecules in zebrafish has facilitated their transition into clinical trials [ 27 ], highlighting the suitability of zebrafish as an exceptional model for preclinical investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different in vivo models, zebrafish catches huge attention for preclinical [ 27 ] and toxicological studies [ 28 ] due to its higher homology with the human genome [ 29 ]. Numerous reports suggest that assessing the preclinical efficacy of small molecules in zebrafish has facilitated their transition into clinical trials [ 27 ], highlighting the suitability of zebrafish as an exceptional model for preclinical investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the safety of high diluted products, Gupta et al (2016) observed the presence of nanoparticles in highly diluted solutions related to patterns of tissue health in zebrafish embryos (Danio rerio) using electron microscopy technique. No toxicity was identified for the embryos (studied by the incidence of malformation, edema, necrotic or apoptotic cell processes, and death), even at different times of exposure.…”
Section: Resultsmentioning
confidence: 99%
“…The zebrafish model is a vertebrate model that is gaining attention for preclinical drug toxicity and drug screening applications. In zebrafish embryos, cardiovascular, nervous and digestive systems develop in less than 1 w. Therefore their early life stages are most prone to the adverse effects of any external substances [30,31] .…”
Section: Resultsmentioning
confidence: 99%